Shedding Light on Cancer: Noninvasive fluorescence-based approaches for detecting and assessing functional events associated with pre-cancers. - Xylas, Joanna. (2017)
Abstract: The most prevalent human diseases, such as cancer, diabetes, and obesity, involve abnormal metabolic states that lead to severe tissue dysfunction. Noninvasive methods that provide spatially resolved metabolic information could substantially advance our understanding of these diseases, leading to better detection and treatment methods. Here, we report on the capabilities of nonlinear microscopy as a high-resolution, label-free optical tool for characterization of cells and tissues. Specifically, we assess healthy and precancerous human papillomavirus (HPV) models with the goal of associating functional tissue changes with optical biomarkers. Through the endogenous fluorescence of keratins, lipids, and nicotinamide and flavin adenine dinucleotides (NADH and FAD, respectively), we quantify modifications in tissue structure as well as the optical redox ratio of FAD/(NADH+FAD), which reflects cell metabolic state. To date, direct comparison between detected optical redox and actual biochemical changes have been elusive. We show NADH and FAD fluorescence signals are strongly correlated to NADH and FAD concentrations as measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Furthermore, since NADH fluorescence emanates primarily from mitochondria, we present a novel Fourier-based image processing method to probe fine changes in mitochondrial features. Due to the interdependence of mitochondrial structure and function, these mitochondrial metrics provide a complimentary measure of cell function. We demonstrate that together, these optical parameters are sensitive to structural and functional changes induced by differentiation, disease, and aberrant cell signaling. Such methods could significantly contribute to the elucidation of cellular and extracellular events that incite and support cancer progression, leading to better methods for detection and treatment.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Irene Georgakoudi.; Committee: David Kaplan, Jonathan Garlick, Nikiforos Kollias, and Karl Munger.; Keywords: Biomedical engineering, Biophysics, and Oncology.